(3GdeHShW aj GdEeGeIs - (3YHO GdfHj Hf SYO GdLRGFQjs ((3SHW GdeDda ; eMeO GdLhGO Hf Ydj GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3agPg fHPI eJYdbI HGdEeGeI GdJj JGgJ Ybhd GdeJHMQjf HCMcGegG hTGgJ CacGQ GdYGQajf HCMhGdgG eY chfgG CUdG ef CUhd GdOjf ceG GbJVJg GdMceI hOdJ Ydjg GdHQGgjf MJi JhGJQ Yf NjQ GdHQjI (B...s
(3BNQgG (B:s
... (3hGf jYGbH ef CVeQ aj gPg GdYbGFO HYOeG ChVMfGg TQG haSGOG hCXgQ ajeG JdhfGg JYUHG hYfGOG HCTO GdYbGH hjYPHg Cfcd GdYPGH hjLGRjg Ydi TQg hbHM fjJg hjaVMg aj SQg hYdGfjJg (B.s
(3efShNI Ydi fSNI HNW SYO Hf Ydj GdHMQGfj , Yf fSNI HJGQjN QeVGf , (B1043 (3, Yf fSNI efShNI Yf eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B19 - 37 ( 280 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds